Substance use and mental diagnoses among adults with and without type 2 diabetes: Results from electronic health records data. (1st November 2015) - Wu, Li-Tzy; Ghitza, Udi E.; Batch, Bryan C.; Pencina, Michael J.; Rojas, Leoncio Flavio; Goldstein, Benjamin A.; Schibler, Tony; Dunham, Ashley A.; Rusincovitch, Shelley; Brady, Kathleen T.
Highlights: Prevalence of type 2 diabetes mellitus (T2DM) has increased substantially. Comorbid T2DM and substance use disorders (SUD) increase morbidity. The extent of T2DM and SUD related comorbidities was examined. Prevalence of all psychiatric categories was elevated in adults with T2DM. Adults with T2DM had more SUD related comorbidities than those without. Abstract: Background: Comorbid diabetes and substance use diagnoses (SUD) represent a hazardous combination, both in terms of healthcare cost and morbidity. To date, there is limited information about the association of SUD and related mental disorders with type 2 diabetes mellitus (T2DM). Methods: We examined the associations between T2DM and multiple psychiatric diagnosis categories, with a focus on SUD and related psychiatric comorbidities among adults with T2DM. We analyzed electronic health record (EHR) data on 170, 853 unique adults aged ≥18 years from the EHR warehouse of a large academic healthcare system. Logistic regression analyses were conducted to estimate the strength of an association for comorbidities. Results: Overall, 9% of adults ( n  = 16, 243) had T2DM. Blacks, Hispanics, Asians, and Native Americans had greater odds of having T2DM than whites. All 10 psychiatric diagnosis categories were more prevalent among adults with T2DM than among those without T2DM. Prevalent diagnoses among adults with T2MD were mood (21.22%), SUD (17.02%: tobacco 13.25%, alcohol 4.00%, drugs 4.22%), and anxiety diagnoses (13.98%). Among adults with T2DM, SUD was positively associated with mood, anxiety, personality, somatic, and schizophrenia diagnoses. Conclusions: We examined a large diverse sample of individuals and found clinical evidence of SUD and psychiatric comorbidities among adults with T2DM. These results highlight the need to identify feasible collaborative care models for adults with T2DM and SUD related psychiatric comorbidities, particularly in primary care settings, that will improve behavioral health and reduce health risk.